Characterization of the complete mitochondrial genome of Culex vishnui (Diptera: Culicidae), one of the major vectors of Japanese encephalitis virus - Li, Le-Yan; Deng, Yuan-Ping; Zhang, Yu; Wu, You; Fu, Yi-Tian; Liu, Guo-Hua; Liu, Jin-Hui (Parasitology research (1987), 2023)
Culex mosquitoes (Diptera: Culicidae) can transmit a variety of arthropod-borne viruses (arboviruses), causing human and animal diseases. Cx. vishnui , Cx. pseudovishnui , and Cx. tritaeniorhynchus are three representative species in Culex vishnui subgroup, which are widely distributed in southeast Asia, and they have been proved as the main vectors transmitting Japanese encephalitis virus (JEV) that could cause human infectious mosquito-borne disease across Asia. However, the epidemiology, biology, and even molecular information of those mosquitos remain poorly understood, and only the mitochondrial genome (mitogenome) of Cx. tritaeniorhynchus has been reported in these species. In the present study, we sequenced and annotated the complete mitogenome sequence of Cx. vishnui which was 15,587 bp in length, comprising 37 genes. Comparisons of nucleotide and amino acid sequences between Cx. vishnui and Cx. tritaeniorhynchus revealed that most genes within Culex vishnui subgroup were conserved, except atp 8, nad 1, atp 6, and nad 6, with differences of 0.4 ( rrn S) — 15.1% (tRNAs) and 0 ( nad 4L) — 9.4% ( atp 8), respectively, interestingly suggesting the genes nad 4L and rrn S were the most conserved but atp 8 gene was the least. The results based on nucleotide diversity also supported a relatively uniform distribution of the intraspecific differences in Cx. vishnui and Cx. tritaeniorhynchus with only one highly pronounced peak of divergence centered at the control region. Phylogenetic analyses using concatenated amino acid sequences of 13 protein-coding genes supported the previous taxonomic classification of the family Culicidae and the monophyly of tribes Aedini, Culicini, Mansoniini, and Sabethini. The present study revealed detailed information on the subgroup Culex vishnui , reanalyzed the relationships within the family Culicidae, provided better markers to identify and distinguish Culex species, and offered more markers for studying the molecular epidemiology, population genetics, and molecular phylogenetics of Cx. vishnui .